Multiple sclerosis. (September 2016) - Raffel, Joel; Wakerley, Benjamin; Nicholas, Richard
Abstract: Multiple sclerosis (MS) is an autoimmune disease of the central nervous system (CNS) and the most common cause of disability among young adults. Most patients present with a relapsing–remitting illness, characterized by discrete episodes of focal neurological deficit with temporal and anatomical dispersion in the CNS. The introduction of diagnostic criteria integrating magnetic resonance imaging has enabled earlier diagnosis and guides earlier intervention in this chronic disease. Although the underlying cause of MS remains unknown, recent advances in molecular immunology have brought about a new wave of immunotherapies that can stop relapses and may delay progression. Given the emergence of more effective therapies, the recognition of relapses and the symptom management of continuing complications are important roles for all clinicians who encounter patients with MS.